A Cross Sectional Study for Assessment of the Pattern of Partial Edentulism in Various Municipalities of Kavre District - Basnyat, S KC; Prajapati, D; Mahanta, S (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Partial edentulism refers to missing one or more natural teeth but not all. Classifying the partial edentulous arches is necessary as it helps in treatment planning, designing and recognition of prosthetic support for removable partial denture. The main aim of this study was to access patterns of partial edentulism among patients and determine its association with socio-demographic parameters. Methods: Patients from various municipalities of Kavre district were selected for the study. Total of 206 patients were selected. The study was divided into two part. Questionnaire related to demographic data and intraoral examination to evaluate the pattern of partial edentulism according to Kennedy’s Classification and Applegate’s rule. The chi-square test was used to determine the association between Socio-demographic variables and pattern of partial edentulism. Statistical evaluation will be done using the Statistical Package for Social Sciences (SPSS 20.0), the level of significance set at p-value <0.05. Result: The number of partially edentulous was less in the age group 20-30 years 38 (27.33%) and 45(28.48%) respectively, whereas, it was high in age group above 50 years 52 (37.41 %) and 57 (36.08 %) respectively. Kennedy’s Class III was the most common type of partial edentulism in both maxillary arch 62 (48.82%) and mandibular arch 71 (46.71%) followed by Class I in both maxilla 31(24.41%) and 38(25%). The least common type of partial edentulism was found to be Class IV. Among the modifications Class III Modification I was the most prevalent condition in both maxillary 17 (27.42%) and mandibular arch 22 (30.9%). Conclusion: The study showed that age had statistically significant association with different classes of partial edentulism in both maxillary and mandibular arches. Whereas, gender had no association with the patterns of partial edentulism.